2019
DOI: 10.1016/j.bpj.2019.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Site-Specific Peptide Probes Detect Buried Water in a Lipid Membrane

Abstract: Transmembrane peptides contain polar residues in the interior of the membrane, which may alter the electrostatic environment and favor hydration in the otherwise nonpolar environment of the membrane core. Here, we demonstrate a general, nonperturbative strategy to probe hydration of the peptide backbone at specific depths within the bilayer using a combination of site-specific isotope labels, ultrafast two-dimensional infrared spectroscopy, and spectral modeling based on molecular dynamics simulations. Our res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 90 publications
2
14
0
Order By: Relevance
“…Our results could possibly explain the earlier stages of water permeability findings of antimicrobial peptides that favor water penetration in bacterial membranes even at very low peptide concentrations, without destroying the membrane integrity. 92–95 However, simulations with higher peptide concentrations and larger membranes should be performed to confirm the positive correlation between peptide concentration and water flow and concentration within membranes.…”
Section: Discussionmentioning
confidence: 99%
“…Our results could possibly explain the earlier stages of water permeability findings of antimicrobial peptides that favor water penetration in bacterial membranes even at very low peptide concentrations, without destroying the membrane integrity. 92–95 However, simulations with higher peptide concentrations and larger membranes should be performed to confirm the positive correlation between peptide concentration and water flow and concentration within membranes.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrafast vibrational spectroscopy is relatively established for proteins, and some of the earliest ultrafast spectroscopic investigations of lipid membranes used membrane peptides to probe the local environment, , finding that the electrostatic environment is much more heterogeneous near the headgroup region than in the hydrophobic core . Using isotope-labeled peptide probes, we recently found that water formed H-bonds to the peptide even where the peptide was buried in the hydrophobic region of the membrane . This study, which used a transmembrane helix with a high percentage of hydrophilic residues, suggested that the presence and composition of transmembrane proteins influences the solvation environment within the bilayer core .…”
Section: Model Systems and Case Studiesmentioning
confidence: 99%
“…Where vibrational probes access different components of the membrane environment, the studies discussed here converge on several key conclusions: (1) Water dynamics near the interface are slow compared to those in bulk water; (2) Interfacial dynamics are sensitive to headgroup structure and membrane composition; (3) Ions, osmolytes, and transmembrane peptides all affect lipid interfacial dynamics; however the nature of the effect is difficult to predict as its origin depends on multiple factors. Ultrafast spectroscopy, interpreted through the lens of MD simulations, allows an atomistic interpretation of the membrane environment that is not accessible by either technique alone. , …”
Section: Future Prospectsmentioning
confidence: 99%
See 1 more Smart Citation
“…(32)(33)(34) When coupled with isotope labeling methods, 2D IR is capable of single-residue structural resolution. (35)(36)(37)(38)(39)(40)(41)(42)(43)(44) Although the vast majority of these studies have focused on β-sheet peptides, several reports have employed 2D IR and isotope labeling to characterize helical peptides. (45)(46)(47)(48) It is important to note that both hydrogen bonding interactions and vibrational coupling affect the observed frequency of the amide I' vibrational transition.…”
mentioning
confidence: 99%